Variations in antibiotic use across India: multi-centre study through Global Point Prevalence survey. Issue 3 (November 2019) - Singh, S.K.; Sengupta, S.; Antony, R.; Bhattacharya, S.; Mukhopadhyay, C.; Ramasubramanian, V.; Sharma, A.; Sahu, S.; Nirkhiwale, S.; Gupta, S.; Rohit, A.; Sharma, S.; et al.
Summary: The aim of the study was to assess antimicrobial prescribing patterns, and variation in practice, in India. A point prevalence survey (PPS) was conducted in October to December 2017 in 16 tertiary care hospitals across India. The survey included all inpatients receiving an antimicrobial on the day of PPS and collected data were analysed using a web-based application of the University of Antwerp. In all, 1750 patients were surveyed, of whom 1005 were receiving a total of 1578 antimicrobials. Among the antimicrobials prescribed, 26.87% were for community-acquired infections; 19.20% for hospital-acquired infections; 17.24% for medical prophylaxis; 28.70% for surgical prophylaxis; and 7.99% for other or undetermined reasons. Antibiotic prescribing quality indicators, such as reason in notes and post-prescription review score, were low. This PPS showed widespread antibiotic usage, underlining the need for antibiotic stewardship to promote evidence-based practice.